Untargeted metabolomics identified kynurenine as a predictive prognostic biomarker in acute myocardial infarction - Zhang, Xiaolin; Cai, Yi; Su, Xu; Jing, Quanmin; Liu, Haiwei; Na, Kun; Qiu, Miaohan; Tian, Xiaoxiang; Liu, Dan; Wu, Tianxiao; Yan, Chenghui; Han, Yaling (Frontiers in Immunology, 2022)
Objective The occurrence of cardiovascular adverse events in the first year after ST-acute myocardial infarction (STEMI) remains high; therefore, identification of patients with poor prognosis is essential for early intervention. This study aimed to evaluate the prognostic value of metabolomics-based biomarkers in STEMI patients and explore their functional mechanisms. Methods Metabolite profiling was performed using nuclear magnetic resonance. The plasma concentration of Kynurenine (Kyn) was measured using ultraperformance liquid chromatography/electrospray ionization quadruple time-of-flight mass spectrometry. Major adverse cardiac and cerebral events were assessed for 1 year. A functional metabolomics strategy was proposed for investigating the role of Kyn in both vitro and vivo models. Results The adjusted hazard ratios in STEMI patients for Kyn in the 4th quartile 7.12(5.71-10.82) was significantly higher than that in the 3rd quartile 3.03(2.62-3.74), 2nd quartile 1.86(1.70-2.03), and 1st quartile 1.20(0.93-1.39).The incidence of MACCE was significantly different among Kyn quartiles and the highest incidence of MACCE was observed in the 4th quartile when compared with the 1st quartile (9.84% vs.2.85%, P<0.001).Immunofluorescence staining indicated that indoleamine-pyrrole 2,3-dioxygenase (IDO1) was located in the CD68 positive staining area of thrombi from STEMI patients and Kyn was induced in the early phase after myocardial infarction. Kyn could trigger inflammation and oxidative stress of macrophage cells by activation of the Sirt3-acSOD2/IL-1β signaling pathway in vitro. Conclusions Plasma Kyn levels were positively associated with the occurrence of STEMI. Kyn could induce macrophage cells inflammation and oxidative stress by activating the Sirt3-acSOD2/IL-1β pathway following myocardial ischemia injury. Kyn could be a robust biomarker for STEMI prognosis and reduction of Kyn could be beneficial in STEMI patients.